Sex, drugs, and catholic schools private schooling and non-market adolescent behaviors - Figlio, David N.; Ludwig, Jens (NBER, 2000)
The paper examines the effects of private schooling on adolescent non-market behaviors. Differences were controlled between private and public school students by making use of the rich set of covariates available with the NELS micro-dataset. An instrumental-variables strategy that exploits variation across metropolitan areas in the costs that parents face in transporting their children to private schools, which stem from differences in the quality of the local transportation infrastructure, was used. Evidence was found to suggest that relious private schooling reduces teen sexual activity, arrests and the use of hard drugs (cocaine), but not drinking, smoking, gang involvement, or marijuana use.
Keywords: Statistik; Church schools -- United States -- Statistics; Private schools -- United States -- Statistics; Teenagers -- Conduct of life -- United States -- Statistics; USA